2022
DOI: 10.21325/jotags.2022.974
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Fine Dining Restaurant Reviews for Perception of Customers Restaurant Service Quality

Abstract: The purpose of this study is to model the perception of customers’ service quality in fine dining restaurants (FDRs) and to determine customer sentiments towards the service quality. I analyzed 22,104 reviews of 25 restaurants on TripAdvisor through Aspect-Based Sentiment Analysis (ABSA). In terms of n-gram language models, the classification performance of sentiment polarity was tested with Support Vector Machine (SVM), Naive Bayes (NB), C4.5, and Gradient Boosted Trees (GBT). I compared the performance of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This is because employees' behaviour, such as being friendly, polite, helpful, and available does not influence the service quality towards customer preferences (Hanafi, 2019). Polat (2022) asserts that a customer's perception of service quality will be a comprehensive analysis of their dining experience. In contrast, Norazha et al (2022) indicate that the quality of the service at a restaurant is directly impacted by the personnel skills.…”
Section: Discussionmentioning
confidence: 99%
“…This is because employees' behaviour, such as being friendly, polite, helpful, and available does not influence the service quality towards customer preferences (Hanafi, 2019). Polat (2022) asserts that a customer's perception of service quality will be a comprehensive analysis of their dining experience. In contrast, Norazha et al (2022) indicate that the quality of the service at a restaurant is directly impacted by the personnel skills.…”
Section: Discussionmentioning
confidence: 99%
“…Researchers found that customers are not just buying food and beverage products; they are looking for the services, the atmosphere, and the unforgettable moments, they want to receive individual attention and be personally engaged in a complete dining experience (Aktas-Polat, 2022; Kim et al, 2003; Shock & Stefanelli, 2001; Walker, 2008).…”
Section: Introductionmentioning
confidence: 99%